Tamerlane’s letter to the mamluk sultan Barkuk and Barkuk’s response letter to Tamerlane Dated AH 795 / AD 1393 - Sayfetdinova E.G. (Золотоордынское обозрение)
Purpose: The purpose of this study is to introduce the Russian translation of Emir Timur’s letter to the Mamluk Sultan Barquq and Barquq’s response letter to Tamerlane, both written in 795 AH / 1393, into scientific circulation. Research materials: The texts of these letters were discovered within the pages of al-Makrizi’s work “Kitab al-Suluk li Ma’rifat Duwal al-Muluk” (“The Book of Ways to Knowledge of the Ruling Dynasties”) Later, these texts were transcribed by Ibn Taghriberdi and Ibn Sirafi. Results and scientific novelty: This article examines the Arabic text of the letters and provides a translation into Russian of Emir Timur’s message to Mamluk Sultan Barquq and Barquq’s response letter from 1393. Emir Timur’s letter, in particular, demanded humility and submission from the Mamluk Sultanate. It’s worth noting that V.G. Tizenhausen, despite using “As-Suluk” by al-Makrizi, did not include the texts of these letters, suggesting they were unrelated to the history of the Golden Horde. However, considering that diplomatic relations were maintained during this period between the Golden Horde and Mamluk Egypt, and that Mamluk Sultan Barquq supported the Golden Horde’s Khan Toktamysh, these letters could provide valuable information about the relationship between these two states. This study marks the first Russian translation of both texts. While Emir Timur’s message may not contain sensational revelations, it does clarify essential details about the late 14th-century situation and contributes to a better understanding of the historical ties between the Horde and the Mamluk Sultanate.